The Role of Technology in Education in Asia: Implementation and Its Impact on Learning Quality - Yasuli Bindulem; Tina Muhardika Handayani (International Journal of Advanced Research, 2025)
This study investigates the implementation of educational technology (EdTech) across diverse Asian contexts and its multifaceted impact on learning quality. Through a mixed-methods sequential explanatory design—combining large-scale surveys (842 schools, 5,638 participants) and in-depth case studies in 8 schools—the research reveals significant disparities in infrastructure, teacher readiness, and pedagogical integration. Urban schools in high-income economies (e.g., Singapore, South Korea) reported near-universal device/broadband access (95–100%), while rural institutions in lower-middle-income countries (e.g., Indonesia, Philippines) faced critical gaps (25–40% access). Teacher self-efficacy in Technological Pedagogical Content Knowledge (TPACK) emerged as the strongest predictor of successful implementation: schools with structured training programs exhibited 3.2× higher adoption of transformative practices (SAMR’s Modification/Redefinition levels). Technology’s impact diverged sharply by implementation depth. Advanced integration (SAMR Modification/Redefinition) correlated strongly with enhanced 21st-century skills—45% higher student engagement, 37–44% gains in critical thinking and collaboration (*r* = 0.71)—but showed minimal effect on standardized test scores (+2.1–2.5%, *p* = 0.38). The digital divide exacerbated inequities: students without home internet scored 28% lower on digital literacy. Hybrid learning models with community support reduced this gap by 19%. Barriers to emerging technologies (AI/VR) included cost (78% of schools), training gaps (64%), and ethical concerns (49%). The study concludes that EdTech amplifies existing inequalities without equity-focused interventions. Success hinges on culturally aligned policies, sustained teacher development, and redefining "learning quality" beyond academic metrics. Technology alone cannot transform education; its efficacy depends on equitable infrastructure, pedagogical empowerment, and systemic support.